2009
DOI: 10.1051/0004-6361/200911869
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different type Ia supernova progenitors on Galactic chemical evolution

Abstract: Aims. Our aim is to show how different hypotheses about type Ia supernova progenitors can affect Galactic chemical evolution. Supernovae Ia are believed to be the main producers of Fe and the timescale with which Fe is restored into the interstellar medium depends on the assumed supernova progenitor model. This is a way of selecting the most appropriate progenitor model for supernovae Ia, a still debated issue. Methods. We include different type Ia SN progenitor models, identified by their distribution of time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
127
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 57 publications
(90 reference statements)
15
127
0
Order By: Relevance
“…4 Matteucci et al (2006Matteucci et al ( , 2009; Yates et al (2013); all these studies agree that the average number of prompt Type Ia SNe can vary from ∼ 15 per cent to a maximum of ∼ 30 per cent with respect to the integrated number of Type Ia SNe, hence a percentage which should be lower than the 50 per cent assumed by Mannucci et al (2006), although these authors concluded that for their data also a percentage of 30 per cent could be acceptable. Finally, the models with the double degenerate scenario (dashed-dotted red curves) predict a steeper declining trend of the [α/Fe] ratios than the single degenerate scenario as first Type Ia SNe explode.…”
Section: Exploring the Effect Of Different Dtds For Type Ia Snementioning
confidence: 82%
“…4 Matteucci et al (2006Matteucci et al ( , 2009; Yates et al (2013); all these studies agree that the average number of prompt Type Ia SNe can vary from ∼ 15 per cent to a maximum of ∼ 30 per cent with respect to the integrated number of Type Ia SNe, hence a percentage which should be lower than the 50 per cent assumed by Mannucci et al (2006), although these authors concluded that for their data also a percentage of 30 per cent could be acceptable. Finally, the models with the double degenerate scenario (dashed-dotted red curves) predict a steeper declining trend of the [α/Fe] ratios than the single degenerate scenario as first Type Ia SNe explode.…”
Section: Exploring the Effect Of Different Dtds For Type Ia Snementioning
confidence: 82%
“…In the so-called single degenerate scenario, a C-O white dwarf (WD) in a close binary system explodes due to gas accretion from a companion in a binary system. Another proposed scenario for Type Ia SNe is the so-called double degenerate case, where two WDs merge, thus triggering the explosion (see Matteucci et al 2009 and references therein). Matteucci et al (2009) Greggio & Renzini (1983) and Matteucci & Greggio (1986) and is expressed as (see more details in Matteucci 2001)…”
Section: Appendix B: the Chemical Evolution Model Adopted In This Workmentioning
confidence: 99%
“…Kobayashi et al 1998;Greggio 2005;Matteucci et al 2009). We chose the following form, given in Kawata & Gibson (2003):…”
Section: Making Chemical Evolution Tracks (Part A)mentioning
confidence: 99%